Royal Images and Sacred Elements in Norman-Swabian and Angevin-Aragonese Kingdom of Sicily - Vagnoni, Mirko (Eikón / Imago, 2013)
This paper analyses the royal images and the sacred elements; or rather, it studies the pictures of the kings of Sicily in Norman-Swabian and Angevin-Aragonese period (1130- 1343) produced inside the court with an official intent, and it examines their meaning regarding the royal sacrality of the king there represented: in other words, the relationship of the sovereign with the sacred element. In this way, it will achieve, regarding this matter, a different position in comparison with the previous interpretations given by historiography.